Pengembangan Training Kit Mini Amplifier untuk Meningkatkan Hasil Belajar Siswa Kelas XI Teknik Audio Video - Berliana Rahma Salsabila; Ali Nur Fathoni; Nur Kholis; Farid Baskoro (Universitas Nahdlatul Ulama Blitar, 2026)
This study aims to develop and evaluate the feasibility of a Mini Amplifier Training Kit as a practical learning tool to improve the learning outcomes of Grade XI students in the Audio-Video Engineering program. The development was motivated by the limited availability of practical facilities that enable students to gain direct experience in operating and understanding audio amplifier systems. This study employed a Research and Development (R&D) approach using the ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation stages. The developed product was assessed based on validity, practicality, and effectiveness. Expert validation results showed that the material component achieved a score of 96%, while the media component obtained 94%, indicating a very high level of validity and feasibility. The practicality assessment based on student response questionnaires resulted in a positive score of 98%, demonstrating that the training kit is easy to operate and supports practical learning activities effectively. Furthermore, a Paired Sample t-Test produced a significance value of 0.000 (p < 0.05), indicating a significant improvement in students’ learning outcomes after using the training kit. The N-Gain score of 0.55 was categorized as moderate. Overall, the Mini Amplifier Training Kit is highly valid, highly practical, and effective, making it suitable for practical learning in Audio-Video Engineering.